2011
DOI: 10.1899/11-044.1
|View full text |Cite
|
Sign up to set email alerts
|

Substrate roughness affects stream benthic algal diversity, assemblage composition, and nestedness

Abstract: Heterogeneity generated by irregularities on the surface of streambed substrates is an important determinant of local species diversity of algae. However, few investigators have examined the effects of substrate roughness on the composition of algal growth forms and on patterns of species distribution. We examined the influence of substrate roughness on stream benthic algal assemblages through a field experiment with 2 treatments (smooth and rough artificial substrates for algal colonization). We assessed whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 34 publications
4
60
0
3
Order By: Relevance
“…Microstructures play a crucial role in diatom attachment (e.g. Wu et al 2013), which consequently alter the benthic assemblage composition at later successional stages (Schneck et al 2011). Accordingly, in our study we observed strong substrate specific differences, with Cocconeis dominating in the smoother microsubstrate surfaces, where its firmly attachment mode presents a greater resistance to the drag forces of the flow (Gari and Corigliano 2007).…”
Section: Discussionmentioning
confidence: 49%
“…Microstructures play a crucial role in diatom attachment (e.g. Wu et al 2013), which consequently alter the benthic assemblage composition at later successional stages (Schneck et al 2011). Accordingly, in our study we observed strong substrate specific differences, with Cocconeis dominating in the smoother microsubstrate surfaces, where its firmly attachment mode presents a greater resistance to the drag forces of the flow (Gari and Corigliano 2007).…”
Section: Discussionmentioning
confidence: 49%
“…Then, nestedness was calculated for each observed matrix and for 10 random matrices generated by each null model to obtain two sets of 10 pairs of nestedness values (the observed value and its respective value in each null model). A paired t-test was performed for each null model to test if the observed nestedness was larger than expected (Schneck et al, 2011), using the R environment (R Development Core Team, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Here, instead of comparing each observed value to the distribution of the simulated functional dissimilarity separately for all the 276 pairwise comparisons, we opted to conduct a paired t test so that the results would highlight the pattern for the complete dataset and not for each pairwise comparison separately. A similar approach was used by Schneck et al (2011b) and by Both & Melo (2015) for other randomization tests.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies that analyzed different aspects related to algal biological traits showed that algal life form, adherence, and locomotion are key traits that determine algae response to light (Lange et al, 2011), nutrients (Passy, 2007;Piggott et al, 2012), sediment deposition (Piggott et al, 2012), disturbance (Passy, 2007;Schneck & Melo, 2012), substrate roughness (Schneck et al, 2011b), and dispersal patterns (Wetzel et al, 2012). In this sense, it is important to understand not only the patterns regarding the dissimilarity in species composition but also the patterns associated with functional dissimilarity.…”
Section: Introductionmentioning
confidence: 99%